Analysis of The Quality of Business Ethics Strategy And Islamic Business Management Concept of Islamic Private Hospitals - Frastuti, Melia; Munthazor, Ahmad Widad; Zahra, Putri Auliya (Indonesian Journal of Accounting and Governance, 2025)
This study aims to identify the causes of the absence of a Sharia Supervisory Board (DPS) in Islamic hospitals in Pekanbaru city, as well as the presence of unprofessional experts and employees, ineffective hospital staff coordination and inadequate future performance planning. This study used a combined method of quantitative and qualitative data utilizing the Analytic Network Process (ANP) approach. ANP is an analysis method used to make decisions in complex situations, especially when there are interdependencies between various factors. The study found four findings: (1) Future hospital performance planning is fulfilled, (2) Experts and employees are selected professionally with the highest score of 27%. (3) Effective staff coordination score is 26%, (4) forming a Sharia Supervisory Board (SSB) has the lowest score of 20%.  This study found that, out of seven Islamic hospitals, only one has a disaster preparedness system (DPS). The director, as the highest-ranking leader, gave the lowest possible score when answering the question about the problems faced by hospitals without a DPS, with a score of 0.099, while experts and regulators gave a score of 0.250. In accordance with DSN MUI No. 107/DSN-MUI/X/2016 concerning Guidelines for Organizing Hospitals Based on Sharia Principles, a sharia hospital must have a DPS to obtain certification. The implementation of DPS is crucial for supervising and resolving problems within hospitals and with stakeholders.